Perchlorate Levels in Soil and Waters from the Atacama Desert - Escudey-Castro, A; Escudey-Castro, A (Springer New York LLC, 2014)
Perchlorate is an anion that originates as a contaminant in ground and surface waters. The presence of perchlorate in soil and water samples from northern Chile (Atacama Desert) was investigated by ion chromatography- electrospray mass spectrometry. Results indicated that perchlorate was found in five of seven soils (cultivated and uncultivated) ranging from 290 ± 1 to 2,565 ± 2 ?g/kg. The greatest concentration of perchlorate was detected in Humberstone soil (2,565 ± 2 lg/kg) associated with nitrate deposits. Perchlorate levels in Chilean soils are greater than those reported for uncultivated soils in the United States. Perchlorate was also found in superficial running water ranging from 744 ± 0.01 to 1,480 ± 0.02 lg/L. Perchlorate water concentration is 30-60 times greater than levels established by the United States Environmental Protection Agency (24.5 ?g/L) for drinking. © Springer Science+Business Media 2013.